Personnel management system improvements in Kazakhstani companies in the context of globalization - Zaitseva, P. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2020)
Globalization affected various areas of human activity and one of them is the personnel management systems. The question of globalization improvements in the staff management systems was already discussed by different researchers, however, Kazakhstani companies were not studied well. The outcomes of the research were intended to evaluate human resource management in Kazakhstani companies and to define problematic areas. Thus, the research questions are: “How personnel management systems have changed in the process of mergers and acquisitions in Kazakhstani companies?”, “How international expansion affected Kazakhstani companies and their approach to personnel management?”, “How international standards that appeared as a consequence of globalization affect Kazakhstani companies?” Various methods of research were applied to investigate the stated problem. The first method was a qualitative analysis, which included a secondary research to find out the main impacts of mergers and acquisitions and international cooperation. The second method was a quantitative analysis that included a questionnaire to find out public opinion and understand what Kazakhstan workers think about the personnel system improvements. Improvements refer to changes in company structure. The results outlined that personnel management systems in `Kazakhstan are in transition phase. Employees that worked in both international and Kazakhstani companies prefer working in international companies, consequently, personnel management systems in Kazakhstan need further development. This dissertation differentiates international and Kazakhstani practices in a sphere of staff management and its improvement. Thus, workers from both international and local companies were surveyed. Furthermore, different aspects of globalization were evaluated, which give exact conclusions about the change.
Keywords: personnel management, globalization, Kazakhstan